Mycorrhizal allies: synergizing forest carbon and multifunctional restoration - Li, Tengteng; Phillips, Richard P; Rillig, Matthias C; Angst, Gerrit; Kiers, E Toby; Bonfante, Paola; Eisenhauer, Nico; Liu, Zhanfeng (Trends in ecology & evolution, 2025)
While forest degradation persists across many regions, restoration efforts have predominantly targeted aboveground carbon, often overlooking critical belowground ecosystem functions. Plant-mycorrhizal associations - key connectors between aboveground and belowground biodiversity - can help to enhance both carbon storage and forest multifunctionality; yet their explicit integration into restoration frameworks remains limited. By synthesizing recent advancements, we highlight the role of plant-mycorrhizal diversity in enhancing soil carbon pools and supporting multiple ecosystem functions. By examining evidence-based restoration cases, we propose a framework linking plant-mycorrhizal associations to sustainably restore resilient and multifunctional forest ecosystems. Incorporating the functional traits of plant-mycorrhizal associations into restoration strategies provides a pathway to effectively address the interconnected biodiversity and climate crises.
Keywords: forest restoration; soil carbon sequestration; particulate organic matter; ecosystem multifunctionality; mineral-associated organic matter; plant–mycorrhizal associations